Family’s Support and Exclusive Breastfeeding Experience During the Covid-19 Pandemic, in Palu: A Cross Sectional Study - Khairunnisaa; Nur Mila Sari; Rifka Haristantia; Nur Azizah Azzahra (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Exclusive breastfeeding coverage in Bulili Health Center is only around 37,7%, very far from the target of SPM 80%. During the COVID-19 pandemic, quarantine situations, activity restrictions and other worst conditions were very difficult experiences and required family support. Objective: The aim of this research is to determine the relationship between family support and exclusive breastfeeding behavior based on the experiences of breastfeeding mothers during the COVID-19 pandemic. Method: Cross sectional design, and self-administered online questionnaire on 111 mothers who have babies aged 6-24 months in working area of Bulili Health Center Palu City. The Research used univariate and bivariate analyzez. Result: The results showed that exclusive breastfeeding mothers was 40,5%. Family support is related to exclusive breastfeeding. Emotional, assessment and informational support from family are supports related to exclusive breastfeeding Conclusion: During the COVID-19 pandemic, family support cannot be ignored for the success of exclusive breastfeeding. Therefore, there is a need for cross-sector cooperation in implementing digital-based communication, information and education to collect informationsupport and movement in public education efforts regarding exclusive breastfeeding during the COVID-19 pandemic.